2022
DOI: 10.1002/anie.202113156
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules Modulate Liquid‐to‐Solid Transitions in Phase‐Separated Tau Condensates

Abstract: In Tau protein condensates formed by the Liquid-Liquid Phase Separation (LLPS) process, liquidto-solid transitions lead to the formation of fibrils implicated in Alzheimer's disease. Here, by tracking two contacting Tau-rich droplets using a simple and nonintrusive video microscopy, we found that the halftime of the liquid-to-solid transition in the Tau condensate is affected by the Hofmeister series according to the solvation energy of anions. After dissecting functional groups of physiologically relevant sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…In one of the few systematic studies of its kind, Jonchhe et al found that hydrophobic moieties in small molecules delay the onset of a liquid-to-solid phase transition in tau LLPS droplets. 151 In the same work, TMAO is shown to be an especially potent inhibitor of the liquid-to-solid transition, which is consistent with the observation that amphiphilic compounds like bis-ANS and ATP can drive LLPS.…”
Section: Noncovalent Small-molecule Chemical Tools For Modulating Llp...supporting
confidence: 77%
“…In one of the few systematic studies of its kind, Jonchhe et al found that hydrophobic moieties in small molecules delay the onset of a liquid-to-solid phase transition in tau LLPS droplets. 151 In the same work, TMAO is shown to be an especially potent inhibitor of the liquid-to-solid transition, which is consistent with the observation that amphiphilic compounds like bis-ANS and ATP can drive LLPS.…”
Section: Noncovalent Small-molecule Chemical Tools For Modulating Llp...supporting
confidence: 77%
“…2b). Using a simple and non-invasive video microscope to track two touching tau-rich droplets, Jonchhe 17 et al observed that liquid eventually turned solid in the LLPS condensate (Fig. 2c).…”
Section: Forming Process and Physiological Mechanismmentioning
confidence: 99%
“…in cells condense into independent droplets of different sizes from weak interactions, dense phase is formed, phase separation occurs and coexists with light phase. [25][26][27] LLPS is a critical process in living organisms and it is isolated from its surroundings and is considered a microenvironment for the biomineralization of minerals. [28,29] The amorphous calcium carbonates (ACC) nucleate and crystallize in droplets.…”
Section: Introductionmentioning
confidence: 99%